2015
DOI: 10.1177/1358863x15594683
|View full text |Cite
|
Sign up to set email alerts
|

Management of mixed arterial venous lower extremity ulceration: A review

Abstract: Mixed arterial venous disease is estimated to affect up to 26% of patients with lower extremity ulcerations. However, its clinical significance and pathophysiology are incompletely understood. Furthermore, there is no consensus on the optimal treatment modality, whether conservative or operative. In this review paper, we describe the current understanding of the pathophysiology of mixed arterial venous lower extremity ulcers. Guidelines for diagnostic tests for patients with mixed arterial venous diseases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 53 publications
0
29
0
3
Order By: Relevance
“…Ulcers of mixed aetiology are also common and they may require modified treatment such as in mixed arterial-venous ulcers (box 2). 2026…”
Section: How To Diagnose Venous Leg Ulcers?mentioning
confidence: 99%
“…Ulcers of mixed aetiology are also common and they may require modified treatment such as in mixed arterial-venous ulcers (box 2). 2026…”
Section: How To Diagnose Venous Leg Ulcers?mentioning
confidence: 99%
“…Another algorithm was published later 23 in a study intended to validate the clinical efficacy and 23 Vowden and Vowden 24 Harding et al 25 Rutherford et al 12 Thomas 26 O'Donnell et al 27 Ratliff et al 28 Eklof et al 10 Vowden and Vowden 24 Widener 29 Harding 30 Krishnan and Nicholls 31 Eberhardt and Raffetto 14 Wittens et al 32 Franks et al 33 Vasquez et al 13 Harding et al 25 Ito et al 34 Lurie et al 11 Wittens et al 32 Tan et al 35 Hedayati et al 19 Ratliff et al 28 Alavi et al 36 Gould et al 37 the cost effectiveness of VLU guidelines in the United States and in the United Kingdom. This study demonstrated that implementation of a guideline for diagnosis and treatment of VLUs resulted in the improvement in diagnosis, decrease in healing time, and an increase in healing rates resulting in lower costs.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…An important factor to consider when managing these wounds is the possibility of concomitant arterial disease: a mixed etiology is estimated to affect up to 26% of patients with lower extremity ulcerations. 19 This article will review the literature on VLUs, specifically treatment algorithms, guidelines, and guidance documents, and provide an up-to-date educational resource for practitioners new to the field. The literature search for venous insufficiency classifications and treatments was conducted in PubMed and Embase in June 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed arterial venous disease is estimated to affect up to 26% of patients with lower extremity ulcerations, however their pathophysiology is not well studied. 22 Mixed venous arterial ulcers usually combine the clinical characteristics of venous leg ulcers and arterial ulcers. They are located in the medial or lateral aspects of the leg, and circumferential extension is not uncommon (Figure 3).…”
Section: Mixed Venous Arterial Leg Ulcersmentioning
confidence: 99%
“…In these cases, the clinical suspicion is important and a thorough arterial and venous evaluation should be performed. 22…”
Section: Mixed Venous Arterial Leg Ulcersmentioning
confidence: 99%